Anticoagulant Protection in Surgery - Storm, Ole (Thrombosis and Haemostasis, 1958)
An evaluation has been made as to whether it is possible to perform operations on patients with tumors of the lungs and with mitral stenosis when the prothrombin-proconvertin-level is reduced by the use of dicumarol. It has been shown that these operations may be performed without the risk of uncontrollable bleedings when prothrombin and proconvertin are reduced to a therapeutic effective level. The prophylaxis seems to protect the patients against the uncontrollable risk of postoperative thromboembolic accidents. The conditions necessary for performing these operations are: the daily control of the P-P.-level, a reliable method for the determination of prothrombin and proconvertin, a meticulous operative hemostasis and the availability of vitamin Kı.